2016
DOI: 10.1152/ajpendo.00104.2016
|View full text |Cite
|
Sign up to set email alerts
|

Proposed mechanisms for oligonucleotide IMT504 induced diabetes reversion in a mouse model of immunodependent diabetes

Abstract: Ϫ1 ·day Ϫ1 ip for 5 consecutive days). We determined blood glucose, glucose tolerance, serum insulin, islet morphology, islet infiltration, serum cytokines, progenitor cell markers, immunomodulatory proteins, proliferation, apoptosis, and islet gene expression. IMT504 reduced glycemia, induced ␤-cell recovery, and impaired islet infiltration. IMT504 induced early blood glucose decrease and infiltration inhibition, increased ␤-cell proliferation and decreased apoptosis, increased islet indoleamine 2,3-dioxygena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 49 publications
(76 reference statements)
1
6
0
Order By: Relevance
“…In vivo studies in T1D diabetes models suggested that IMT504 induced active proliferation, mainly in β‐cells (Bianchi et al, 2010 , 2016 ). Subsequently, we determined the effect of IMT504 on MIN6B1 proliferation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In vivo studies in T1D diabetes models suggested that IMT504 induced active proliferation, mainly in β‐cells (Bianchi et al, 2010 , 2016 ). Subsequently, we determined the effect of IMT504 on MIN6B1 proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…With this in mind, and since IMT504 has both immunomodulatory and regenerative properties, our group started to evaluate this ODN as a possible therapy for T1D in several animal models, finding very promising results in terms of beta cell recovery, improvement on glucose and insulin blood levels, and decrease in beta cell apoptosis, and insulitis and infiltration of CD45+ leukocytes into the pancreas (Bianchi et al, 2010(Bianchi et al, , 2012(Bianchi et al, , 2016(Bianchi et al, , 2021. Nevertheless, these in vivo experiments did not hint to a possible direct effect of IMT504 on βcells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations